EARLY ORAL FEEDING EFFECT ON GASTROINTESTINAL SYMPTOMS AND PATIENTS’ SATISFACTION AFTER CESAREAN DELIVERY UNDER GENERAL ANESTHESIA - L Sekhavat, (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Historically, patients were fasted following abdominal surgery until return of bowel sounds or passage of flatus. The aim of this study was to evaluate the effect of early feeding after caesarean section on the possible adverse gastrointestinal effects and womens satisfaction.METHODS: In a clinical trial at Shahid Sedughi hospital, Yazd, 220 women delivered by cesarean were randomly divided into two groups. A clear liquid drink was given to 110 women in the early feeding group 2 hours after surgery, and to 110 women in the control group 12 hours after surgery. If the drink was tolerated, solid foods were then given. Two groups were compared in terms of bowel sounds, flatus, nausea and vomiting, womens satisfaction and hospital stay. FINDINGS: Early feeding group was earlier in first bowel sound, first post operation flatus and defecation. Regular diet is tolerated earlier in early feeding group than delayed feeding group (8.6±2.1 versus 20.9±5.9 hour, p= 0.00). There were no significant differences in postoperative gastrointestinal complications. Mean duration of hospitalization was 26.6 ± 4.3 h in early feeding group and 54.1 ± 3.8 h in delayed feeding group (p=0.00). The womens satisfaction in the early feeding group was higher than delayed feeding group (79.2 ±12.1 vs 50.1± 13.9, p= 0.01).CONCLUSION: Early oral feeding after cesarean delivery was associated with early tolerated regular diet, low duration of hospitalization, high womens satisfaction and no significant adverse gastrointestinal effects compared with delayed feeding.